Aroma production by Yarrowia lipolytica in airlift and stirred tank bioreactors: differences in yeast metabolism and morphology - Braga, Adelaide (2015)
The production of γ-decalactone from castor oil in batch cultures of Yarrowia lipolytica W29 was compared in stirred tank (STR) and airlift bioreactors. Oxygen mass transfer from air to biphasic medium was characterized in both bioreactors trough correlations for kLa with power input and superficial gas velocity. Different conditions of oxygen transfer rate (OTR) were selected to perform biotransformations and for both bioreactors improvement of γ-decalactone productivity was obtained with OTR increase, with the highest value of 75 ± 10 mg L−1 h−1 being obtained in the STR for a kLa of 113 ± 5 h−1. However, a 2-fold increase in γ-decalactone concentration (around 3 g L−1) was achieved in the airlift compared to STR. Morphological characterization of the yeast cells by quantitative image analysis techniques showed that pneumatic agitation causes less impact in the cells morphology than mechanical agitation. A predominance of somewhat loose cells and quite irregular structures was observed in the STR.